Can the Undocumented Speak? Undocumented Immigrants and Self-Representation - Canelo, Maria José (2020)
Undocumented immigrants usually trust their voices to immigration activists rather than engaging with strategies of visuality to reclaim their rights. The universe of illegal border crossing is about radical experiences of invisibility, misidentification, erasure, dispossession, and disappearance. First person testimonies by undocumented immigrants have, however, seen the light of day throughout the last decade in unsuspected media venues, from the New York Times to the Guardian, small sites of independent journalism, and also some book publications. Revealing their presence, their names, and their faces seems a brave decision, when the risk of deportation is part of their everyday reality. In my reading of their testimonies and the photographs illustrating them, I follow two theoretical lines that engage with the subjectivities of marginalized groups: sociologist Boaventura de Sousa Santos’ elaboration of a post abyssal thinking and cultural critic Nicholas Mirzoeff’s ideas of spaces of appearance and practices of counter visuality. Combining them will allow me to analyze how instances of self-representation by undocumented immigrants in the United States contribute to crafting a new subject position by a group who, by definition, cannot speak because it is deemed non-existent in legal terms. The issue brings back to the discussion Gayatri Spivak’s classical questions on subalternity and power.